Pengaruh Enterprise Risk Management dan Ukuran Perusahaan Terhadap Financial Distress - F., Fitriyani; W, Warno; Anwar, Khoirul (Jurnal Akuntansi, Audit, dan Aset, 2021)
This research aims to find out the influence of enterprise risk management and the size of thecompany on financial distress in manufacturing companies listed on the Indonesia Stock Exchange(IDX) in 2017-2019. The sample data selected as many as 114 manufacturing companies withselection methods based on nonprobability sampling. The tests used in this study include multiplelinear regression tests, T-tests, and F tests. Test results obtained from this study show that variableinterest rates, enterprise risk management, and company size partially have no effect on financialdistress in manufacturing companies. And simultaneously the variables of enterprise riskmanagement and the size of the company have no effect on financial distress in manufacturingcompanies listed on the Indonesia Stock Exchange (IDX) in 2017-2019.